(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2026)
Background: Hypertension is a major risk factor for Chronic Kidney Disease (CKD) often causing subclinical renal damage long before overt symptoms appear. Microalbuminuria, as reflected by the Urinary Albuminto-Creatinine Ratio (UACR) and a decline in estimated Glomerular Filtration Rate (eGFR) are key indicators of early renal impairment. Evaluating these parameters in non-diabetic hypertensive individuals can aid in timely identification of renal involvement. This study aimed to assess the UACR and eGFR in non-diabetic hypertensive patients compared to normotensive individuals attending a tertiary care hospital in Chattogram, Bangladesh. Materials and methods: This hospital-based crosssectional comparative study was conducted at Chittagong Medical College Hospital during the period from January to December 2023. A total of 136 participants were enrolled using purposive sampling and divided into two equal groups: hypertensive (n=68) and normotensive (n=68). Key variables were measured include UACR, eGFR, systolic and diastolic blood pressures, Body Mass Index (BMI) serum creatinine and lipid profile. Results: The prevalence of microalbuminuria was significantly higher in the hypertensive group compared to the normotensive group (33.8% vs. 7.4%, p<0.001). Hypertensive participants had higher mean age, BMI, systolic and diastolic blood pressures compared to normotensive counterparts (p<0.001 for all). The mean eGFR was significantly lower in hypertensive individuals (85.64 ± 14.15 vs. 94.28 ± 14.09 mL/min/1.73 m², p=0.001) while the mean UACR was significantly higher (49.15 ± 10.56 vs. 10.08 ± 1.16 mg/g, p<0.001). Multivariate linear regression identified SBP (b=0.619, p<0.001) as the only independent predictor of UACR levels. No variable independently predicted eGFR in the regression model. A graded relationship was observed between hypertension severity and microalbuminuria, with the highest prevalence noted in stage 2 hypertension (50%). Conclusion: Microalbuminuria is significantly more prevalent among hypertensive patients and is strongly associated with early organ damage. Early detection through routine screening in hypertensive individuals is recommended to prevent long-term complications. JCMCTA 2025 ; 36 (2) : 145-150